Putting the Cart Before the Horse? : Capital Account Liberalization and Exchange Rate Flexibility in China - Prasad, Eswar (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2005)
This paper reviews the issues involved in moving towards greater exchange rate flexibility and capital account liberalization in China. A more flexible exchange rate regime would allow China to operate a more independent monetary policy, providing a useful buffer against domestic and external shocks. At the same time, weaknesses in China's financial system suggest that capital account liberalization poses significant risks and should be a lower priority in the short term. This paper concludes that greater exchange rate flexibility is in China's own interest and that, along with a more stable and robust financial system, it should be regarded as a prerequisite for undertaking a substantial liberalization of the capital account.